المعجم الشعري في الشعر الليبي ديوان ( خواطر الكنانة) إنموذجا: المعجم الشعري في الشعر الليبي ديوان ( خواطر الكنانة) (Elmergib Journal of Human Sciences, 2025)
The Poetic Dictionary of Libyan Poetry, the Diwan "Khawatir Al-Kanana" as a ModelThat known that every poet has his own dictionary that distinguishing him from others, and he sharing some words and phrases with other poets. The Libyan poet is part of the nation's poets who used the Arabic language to express their feelings and thoughts, drawing on the cultures around them. This poet, the subject of this research, that representing one of the contemporary poets. The researcher chosen him to show the sources of his poetic dictionary, supported by evidence that showing the extent of the culture of Libyan poets.This research is consisting of an introduction, a preface that including: an introduction to the poet, an introduction to the collection, and a section on the religious dictionary in which the poet tackled: religious terms such as: Hajj, prayer, fasting, and Eids, quoting their meanings from: the Holy Qur’an and the pure prophetic Sunnah.Topic: Dictionary of Nature, which derived its words from: the picturesque nature with its mountains, plains, sea, and land. Section: Dictionary of Heritage Words, in which he summoned ancient heritage words and expressed them in his poetry; to show us the extent of the poet’s culture and linguistic ability. A conclusion containing the most important results and a list of sources and references.